Pengaruh Komite Pemantau Risiko (KPR) pada Kualitas Pelaporan Keuangan dan Biaya Auditor di Indonesia - Vanessa Annabelle; Rizky Eriandani (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
This journal discusses discusses the effect of the Risk Committee (RC) on financial reporting quality dan audit fees in Indonesia. The purpose is to see if the presence of RC in Indonesia can improve corporate governance to be better. The data used are form all sector nonÂ-financial that listed on Indonesia Stock Exchange (BEI) in the period of 2018 â€“ 2020. This research is a quantitative study with a descriptive design that uses linear regression analysis and data validity tests. The method used in sampling is a non probability purposive judgement sampling. Dependent variable in this research is the financial reporting quality proxied by discretionary accruals (DACC) dan audit fees proxied by logarithm from audit fees. Independent variable in this research is the RC that used dummy variable. The result shows that RC had no significant positive effect to financial reporting quality and had no significant negative effect to audit fees.